New modalities in the treatment of HCV in pre and post - transplantation setting - Araz, Filiz; Durand, Christine M.; Gürakar, Ahmet (Turkish Journal of Gastroenterology, 2015)
Abstract End-stage liver disease and hepatocellular carcinoma (HCC) secondary to hepatitis C virus (HCV) infection are the leading indications for liver transplantation (LT) in developed countries. Recurrence of HCV following LT is universal if the recipient has detectable serum HCV RNA at the time of LT. Recurrent HCV has an accelerated course and is associated with poor long term patient and graft survival. Interferon (IFN)-based regimens have achieved low Sustained Virological Rates (SVR) in this setting and are associated with a high rate of adverse events, resulting in treatment discontinuation. With advances in understanding the HCV life cycle, drugs targeting specific steps, particularly inhibiting the NS3/4A protease, NS5B RNA dependent RNA polymerase and the NS5A protein, have been developed. Sofosbuvir (SOF), a nucleotide analogue inhibitor of NS5B polymerase was the first compound to enter the market. Combinations of SOF with new HCV antivirals from other classes have allowed for IFN-free regimens with low rates of adverse events and SVR rates >90%. With the availability of newer agents, the approach to the treatment of HCV infection during the pre-and post-liver transplantation period has changed. We will hereby review the current status of HCV treatment and discuss the potential future therapies in the transplant setting.